2015
DOI: 10.6000/1927-5129.2015.11.58
|View full text |Cite
|
Sign up to set email alerts
|

Insulinotropic Activity of Methanolic Extract of Mesua ferrea Linn.

Abstract: Mesua ferrea flowers have been used in the Indian traditional medicine for treating various diseases. In present study, the Mesua ferrea flowers methanolic extract (MFME, 200 mg/kg bw) was studied for anti diabetic activity and underlying mechanisms for its activity. In Streptozotocin induced diabetes rats model, MFME treatment enhanced plasma insulin levels by 69.53% (P<0.0001) than the diabetic control rats. In diabetic rats, MFME treatment significantly restored body weight and blood glucose levels to norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Stamens of M. ferrea produced a dose-dependent reduction in blood sugar (hypoglycemia) at a dose of 150 and 300 mg/kg body weight in alloxan-induced diabetic rats [ 64 ]. The methanol extract of M. ferrea flower has shown the antidiabetic activity in streptozotocin-induced diabetic rats and deduced the mechanism [ 65 ]. The extract of M. ferrea flower was proved no acute toxicity in an animal model but exhibited mild lymphocytic infiltration and hepatocyte degeneration [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stamens of M. ferrea produced a dose-dependent reduction in blood sugar (hypoglycemia) at a dose of 150 and 300 mg/kg body weight in alloxan-induced diabetic rats [ 64 ]. The methanol extract of M. ferrea flower has shown the antidiabetic activity in streptozotocin-induced diabetic rats and deduced the mechanism [ 65 ]. The extract of M. ferrea flower was proved no acute toxicity in an animal model but exhibited mild lymphocytic infiltration and hepatocyte degeneration [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The methanol extract of M. ferrea flower has shown the antidiabetic activity in streptozotocin-induced diabetic rats and deduced the mechanism [ 65 ]. The extract of M. ferrea flower was proved no acute toxicity in an animal model but exhibited mild lymphocytic infiltration and hepatocyte degeneration [ 65 , 66 ]. Xanthones and coumarins are predominantly secondary metabolites from Mesua species which display antitumor and antimicrobial, antioxidant, anti-inflammatory, or immunomodulating properties [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Balekari et al, reported that the methanolic extract of Mesua ferrea leaves have promising antidiabetic activity in streptozotocin-induced diabetic rats. It was found that the extract reduced the blood glucose levels and normalized the body weight in diabetic rats [27] .…”
Section: Antidiabetic Activitymentioning
confidence: 96%
“…Another study of antioxidants by using methanolic extract of Nagkesar flower possesses activity against DPPH free-radical, super-oxide and hydrogen-peroxide in scavenging-assays [26] . A study on Nagkesar root methanol polar extract discovered that it was more active than less polar or non-polar extract [27] .…”
Section: Anti-oxidant Activitymentioning
confidence: 99%
“…We can analyse the Ashlesha nakshatra using the relevant Rashi and graha based on the above information. It Roghagnatha: Asrigdara, Raktharshas, Kustha, Kandu, Vrana, visha, Ama dosha, Chardi, Hrullasa, Hikka, Garbhashaya shodhana, Arthava Vyapath Pharmacological activities: Antioxidant activity [4][5][6][7][8][9][10] Analgesic activity 11 Anti-inflammatory activity [12][13][14] Anti-arthritis activity 15 Antispasmodic activity 16 Antivenom activity 17 Antimicrobial & anti-fungal activity [18][19][20][21][22][23][24][25][26] Water disinfectant activity 27 Diuretic activity 28 Anti-haemorrhoid activity [29][30] Wound healing activity 31 Central nervous system depressant and anticonvulsant activity 32 Immunomodulatory and hormone-balancing activities 33 Anti-diabetic activity 34 Hepatoprotective activity. [35][36] Cardioprotective activity .37 Protection against chronic obstructive pulmonary disease (COPD) 38 Anticholinesterase and α-amylase inhibitory activity 6/39 Anticancer activity [40][41] Ayurvedic medicines with Nagkesar as an ingredient:…”
Section: Relationship Between Body Parts and Astrologymentioning
confidence: 99%